2022
DOI: 10.3390/pathogens11101165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Venturia inaequalis in Latvia Revealed by Microsatellite Markers

Abstract: Apple scab caused by the ascomycete Venturia inaequalis is an economically significant disease worldwide. The annual sexual reproduction of V. inaequalis leads to high variation, changes in the population’s genetic structure and adaptations to the changing environment, including overcoming the host’s resistance. The objective of this study is to characterise and assess the genetic diversity of V. inaequalis populations in two main apple-growing regions in Latvia. In total, 143 V. inaequalis isolates were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Most studies suggested weak differentiation between V. inaequalis populations despite being separated by large geographic distances [44][45][46][47][48][49][50], with a few exceptions where mountainous or coastal regions with vastly differing climate conditions were also included in the study [51,52]. Besides environmental factors, host-specialization is among the major evolutionary forces guiding population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies suggested weak differentiation between V. inaequalis populations despite being separated by large geographic distances [44][45][46][47][48][49][50], with a few exceptions where mountainous or coastal regions with vastly differing climate conditions were also included in the study [51,52]. Besides environmental factors, host-specialization is among the major evolutionary forces guiding population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Polish scientist Dux discovered a microsatellite locus in the intron 23 region of insulin-like growth factor receptor 2 and signi cantly associated different genotypes of this locus with high milk yield, high milk fat percentage, and high milk protein level (Dux M et al 2018). Recently, many studies have analyzed STRs and SSRs in plants and microorganisms, for example, genetic diversity of Venturia inaequalis in Latvia (Sokolova et al 2022), STR locus comparison of cherry germplasm in Europe (Ordidge et al 2021), microsatellite loci related to drought tolerance traits in potato (Schumacher et (Hameed et al 2022), relationship between genetic diversity and phylogeny of cattle in Senegal (Sambe et al 2022), relationship between genetic diversity and phylogeny of Siberian black-skinned cattle (Aitnazarov et al 2021), genetic diversity of cattle in Kerala, India, and relationship between STR genetic diversity and quantitative trait variations of bull semen (Gororo et al 2021). There has been limited research on the correlation between microsatellite loci and milk production traits of Holstein cows, and there are no reports on microsatellite locus analysis of Holstein cows in Xinjiang.…”
Section: Introductionmentioning
confidence: 99%